2019
DOI: 10.1111/lasr.12440
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Paradox of Crime Reporting: Are Disadvantaged Victims More Likely to Report to the Police?

Abstract: This study uses an intersectional approach to examine the “paradox” that disadvantaged victims often mobilize the police, despite their distrust and lack of confidence in the law. Data from the National Crime Victimization Survey (1994–2016) were analyzed using logistic regression to model the predicted probabilities of police notification by victims of crime. Economic disadvantage, as measured by family poverty and lack of a high school education, increased the probability that females reported their victimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 103 publications
1
26
1
Order By: Relevance
“…Similar versions of this seeming paradox have been noted in previous research on legal cynicism (e.g. Bell, 2016;Carr et al, 2007;Zaykowski et al, 2019). Indeed, estrangement does not preclude willingness to comply with and resorting to the police.…”
Section: Resentful Reliance On the Policesupporting
confidence: 74%
“…Similar versions of this seeming paradox have been noted in previous research on legal cynicism (e.g. Bell, 2016;Carr et al, 2007;Zaykowski et al, 2019). Indeed, estrangement does not preclude willingness to comply with and resorting to the police.…”
Section: Resentful Reliance On the Policesupporting
confidence: 74%
“…Although we were unable to directly assess the mechanisms underlying these patterns with the NCVS data used in the present study, these results may indicate that reluctance to report to the police—among both Black and White victims—plays a stronger role in predicting actual reporting behavior when incidents are less severe. In other words, whereas prior research has frequently observed increased reporting among Black victims and noted that this pattern is often contrary to theoretical expectations (Zaykowski et al, 2019)—and we find similar patterns when examining more severe victimization—our results indicate that Black victims are not more likely than White victims to report victimization when the incident is less severe.…”
Section: Discussioncontrasting
confidence: 86%
“…Regarding residential violent crimes and violent crimes against minorities, fear of one’s significant other and a lack of trust in the police by racial minority groups may partially explain the shrinking—though still noticeable—seasonality around these crimes in LA. It has been well documented that minority communities in the U.S., at least in part, do not trust (and are therefore less likely to report) crimes to police (Zaykowski et al 2019 ). Additionally, minorities who have come to the U.S. illegally may hesitate to report crimes to the police for fear of deportation (Macias Jr 2019 ).…”
Section: Discussionmentioning
confidence: 99%